OPPORTUNITIES FOR APPLICATION OF THE NEURAMINIDASE INHIBITORS IN TREATMENT AND PREVENTION OF THE FLU - Yu.B. Belan; M.V. Starikovich (Педиатрическая фармакология)
Flu viruses cause yearly epidemics with the lesion of approximately 20% of population. during the increase of the flu sickness rate, it is necessary to take urgent anti epidemic and treatment steps aimed to reduce the spread of an infection as soon as possible and incorporating the application of the specific antiviral medications. The major aims for prescription of the specific antiviral medications in flu treatment are to reduce the duration and severity of the leading disease symptoms, risks of complications, as well as to prevent the lethal out comes. There were developed medications, effectively inhibiting the replication of B flu virus. At present, there are the 1st generation medications available — adamantane derivatives (amantadine and rimantadine) and the 2nd generation medications — neuraminidase inhibitors (oseltamivir and zanamivir). The fast increase of the flu virus resistance towards adamantanes determine the necessity of a wider application of neuraminidase inhibitors, which are highly effective in respect flu viruses of A and B, as well as avian flu virus (h5n1).Key words: neuraminidase inhibitors, adamantanes, oseltamivir, zanamivir, h3n2, h5n1.